Comparison of Meconium DNA Extraction Methods for Use in Microbiome Studies - Stinson, Lisa F.; Keelan, Jeffrey A.; Payne, Matthew S. (Frontiers in Microbiology, 2018)
The establishment of human gut microbiota commences initially in utero. Meconium – the first fecal material passed after birth - can be used to study fetal gut contents; however, processing meconium samples for microbiome studies presents significant technical challenges. Meconium hosts a low biomass microbiome, is tar-like in texture and contains high concentrations of PCR inhibitors. This study aimed to evaluate four different DNA extraction methods to elucidate the most effective method for bacterial DNA recovery and analysis from first-pass meconium. Samples from five infants were collected. 200 mg of meconium from each infant was processed using the following extraction kits: 1) Qiagen QIAamp DNA Stool Mini (QS); 2) Qiagen QIAamp DNA Microbiome (QM); 3) MoBio PowerSoil (PS); 4) MoBio MagAttract PowerMicrobiome (PM). Additionally, Kit PM was employed with a double inhibitor removal treatment step (PM2). Bacterial DNA recovery was assessed by qPCR. Any PCR inhibition in samples was measured by spiking DNA eluates with 0.1 ng of pure Streptococcus agalactiae (GBS) DNA followed by qPCR quantitation. Kit PM yielded the highest average total DNA yield (79.3 ng per gram of meconium). Samples extracted with kit PS had the highest detectable levels of 16SrDNA, with average qPCR Ct values 1.7 cycles earlier than the extraction controls, respectively. The ability of each kit to overcome PCR inhibition varied, with qPCR on GBS-spiked DNA from kits QS, QM, PS, and PM recovering 87.1%, 91.0%, 88.8% and 37.9% GBS DNA, respectively. Double inhibitor removal treatment improved the performance of kit PM, increasing GBS recovery to 56.5%. However, once DNA yield was normalized to the level recovered with the other kits 100% of GBS DNA was detected, suggesting that levels of PCR inhibitors are related to DNA yield from kit PM. Ion Torrent 16S rRNA gene sequencing revealed a high level of inter-kit variation in meconium microbiome structure. In particular, kit QM showed a bias towards extracting Firmicute DNA, while the other kits extracted primarily Proteobacterial DNA. Choice of extraction kit greatly impacts on the ability to extract and detect bacterial DNA in meconium and on the microbiome community structure generated from these samples.